Microwave attenuation of multiwalled carbon nanotube-fused silica composites - Xiang, Changshu; Pan, Yubai; Liu, Xuejian; Sun, Xingwei; Shi, Xiaomei; Guo, Jingkun (Applied physics letters, 2005)
Multiwalled carbon nanotubes (MWCNTs) were used to convert radome materials to microwave absorbing materials. Dense MWCNT-fused silica composites were prepared by hot-pressing technique. The composites exhibit high complex permittivities at X-band frequencies, depending on the content of MWCNTs. The value of the loss tangent increases three orders over pure fused silica only by incorporating 2.5vol% MWCNTs into the composites. The average magnitude of microwave transmission reaches −33dB at 11–12GHz in the 10vol% MWCNT-fused silica composites, which indicates the composites have excellent microwave attenuation properties. The attenuation properties mainly originate from the electric loss of MWCNTs by the motion of conducting electrons.